Etika ASN Dalam Penyelenggaraan Pemerintahan Negara - Y. Gede Sutmasa (Universitas Mahendradatta Denpasar, 2019)
The state civil apparatus (ASN) has a very important role in governmentimplementation of Republic of Indonesia. The main function of ASN is public policyexecution, public service, and adhesive and unifying nation. In the hand of ASN, theexecution of various government affairs was actually carried out.In order to implementation of the function is done effectively, there is code of ethicsmust be obeyed by the ASN. But in reality, there are still many violations of the ASNcode of ethics. The cause is it can be internal of external factors.While the elementsthat influencing the realization of ethics in the organization, according to MagnisSuseno are work environment and supervision/control.Considering the determinants of ASN role in implementing the state government,enforcement of ASN ethics is very important. By knowing the causes of ethical violationsby ASN and the elements that influencing the realization of ethics in theorganization, so that must be done to enforcing the ethics of ASN is, first, enforcingand establishing the corps spirit of ASN through a consistent and continuous coaching;second, controlling by the society and mass media over ASN behavior throughthe available channels; and third, enforcing the discipline and provide strict and clearsanctions for violating the code of ethics by the ASN.